2018
DOI: 10.1039/c8sm01891j
|View full text |Cite
|
Sign up to set email alerts
|

Molecular layers in thin supported films exhibit the same scaling as the bulk between slow relaxation and vibrational dynamics

Abstract: We perform molecular-dynamics simulations of a supported molecular thin film. By varying thickness and temperature, we observe anisotropic mobility as well as strong gradients of both the vibrational motion and the structural relaxation through film layers with monomer-size thickness. We show that the gradients of the fast and the slow dynamics across the layers (except the adherent layer to the substrate) comply, without any adjustment, with the same scaling between the structural relaxation time and the Deby… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 49 publications
(83 reference statements)
3
20
0
Order By: Relevance
“…Finally, we note that there is not direct and trivial relation between the present analysis and previous works addressing the effect of spatial dimension in the dynamics of glassforming liquids [13,14,15]. Hence, the reported equivalence of 2D and 3D scaling is a further indication supporting the idea that the dynamics in bulk and confined glassforming liquids can be described by the same fundamental rules.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Finally, we note that there is not direct and trivial relation between the present analysis and previous works addressing the effect of spatial dimension in the dynamics of glassforming liquids [13,14,15]. Hence, the reported equivalence of 2D and 3D scaling is a further indication supporting the idea that the dynamics in bulk and confined glassforming liquids can be described by the same fundamental rules.…”
Section: Discussionsupporting
confidence: 60%
“…In simulations of supported thin films, Douglas and coworkers showed that, by considering the average dynamics of the film, the bulk-like scaling law between u 2 and τ α is recovered with a slightly different scaling adjustable parameter [13]. Taking into account the strong gradient of mobility in the film via a layer resolved analysis, Leporini and coworkers improved on previous results and showed that the u 2 -τ α correlation is exactly the same of bulk, i.e., it is described by the same master curve with no adjustable parameters [14]. These findings suggest that the dynamics in thin films or confined materials and in their bulk counterpart are controlled by the same fundamental rules.…”
Section: Introductionmentioning
confidence: 99%
“…Working in that direction, we have found positive answers and the present paper collects and reviews a selected part of our results, with a focus on the breakdown of the SE law [29,30]. Even if strictly related, we will not discuss here a study concerning ultrathin molecular films with strong mobility gradients analogous to DH, where the same scaling observed in bulk, Equation (2), has been revealed [61].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the huge difference in time scales, earlier [33] and later theoretical studies [5,34,35,36,37,38,39,40], and experimental ones [41], addressed the rattling process within the cage to understand the slow dynamics, rising a growing interest on the DW factor [8,29,30,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61]. Within this context, most interest has been devoted to the correlations between DW factor and the structural relaxation time τα, which are found to be strong and encompassed by a universal master curve [47]:τα=scriptF(u2)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation